TCL Technology’s Merger and Acquisition of Central Electronics: Analysis of Corporate M&A and Restructuring Strategies - Liu, Li (Transactions on Economics, Business and Management Research, 2024)
Benefiting from national policy support and market economy, China’s semiconductor industry has made significant progress in technological innovation, especially in the context of 5G, smart Internet and big data era, the center of gravity of the industry is shifting from South Korea and Taiwan to mainland China.Through the acquisition of Azeus, which is equipped with profound semiconductor packaging and testing technology, TCL Technology aims to enhance its competitiveness in the semiconductor field, optimize supply chain management and improve product quality control capability. supply chain management and improve product quality control. This paper examines TCL’s acquisition of Azeus and discusses six aspects of the acquisition: overview of the two parties, industry background, progress of the acquisition, performance evaluation (including financial and non-financial), risk analysis, and characteristics of the acquisition. The results show that the acquisition has had a positive impact on TCL’s development in semiconductors and related fields.